Drugs in pregnancy-how safe? - Dutta, Dilip Kumar (New Delhi : Jaypee Brothers Medical Publishers, 2008)
Análisis de riesgos potenciales y beneficios de los medicamentos utilizados en el embarazo destaca el desarrollo del bebé en el útero, teratogénesis, efectos adversos de las drogas, el tabaquismo, las adicciones a las drogas, etc. en el
Contents SECTION A 1. Drugs and pregnancy-overview 2. Development of baby in utero 3. Teratogenesis and other adverse efects of drugs during pregnancy SECTION B 6. Drugs used for medical disorders in pregnancy-effects on the baby 7. Anesthetic and analgesic drugs used during labor-effects on the baby SECTION C 10. Alcohol in pregnancy-how safe? 11. Drug addiction during pregnancy-Its effects on the baby SECTION D 13. Homeopathy drugs during pregnancy 14. Ayurvedic drugs during pregnancy SECTION E 15. Drug induced acute renal failure in pregnancy- management SECTION F 16. Drugs used during breastfeeding-effects on newborn baby SECTION G 17. Role of progesterone and hCG Treatment in early pregnancy SECTION H 18. Drugs used in pregnancy and ists effects on baby an Infants in alphabetical order SECTION G SECTION H
El texto esta en inglés
Incluye bibliografía e índice
Keywords: TRASTORNOS FETALES; EFECTOS EN EL EMBARAZO -- DROGAS; ABUSO DE DROGAS EN EL EMBARAZO; DRUGS IN PREGNANCY